Explanation paradigms leveraging analytic intuition (ExPLAIn) - Jansen, Nils; Nolte, Gerrit; Steffen, Bernhard (Technische Universität Dortmund, 2023)
In this paper, we present the envisioned style and scope of the new topic “Explanation Paradigms Leveraging Analytic Intuition” (ExPLAIn) with the International Journal on Software Tools for Technology Transfer (STTT). Intention behind this new topic is to (1) explicitly address all aspects and issues that arise when trying to, if possible, reveal and then confirm hidden properties of black-box systems, or (2) to enforce vital properties by embedding them into appropriate system contexts. Machine-learned systems, such as Deep Neural Networks, are particularly challenging black-box systems, and there is a wealth of formal methods for analysis and verification waiting to be adapted and applied. The selection of papers of this first Special Section of ExPLAIn, most of which were co-authored by editorial board members, is an illustrative example of the style and scope envisioned: In addition to methodological papers on verification, explanation, and their scalability, case studies, tool papers, literature reviews, and position papers are also welcome.
International journal on software tools for technology transfer; 25(3)
Keywords: Formal methods; Explanation; (Deep) Neural Networks; Deep learning; Rigorous analysis; Decision trees; Random forests; Robustness; Reliability; Verification; (Statistical) model checking; Testing; Competition; 004; Formale Methode; Erklärung; Tiefes neuronales Netz; Deep Learning; Entscheidungsbaum; Robustheit; Zuverlässigkeit; Verifikation; Model Checking; Testen